Solid-State LiDAR based-SLAM: A Concise Review and Application - Nam, Dinh Van; Gon-Woo, Kim (International Conference on Big Data and Smart Computing, 2021)
An efficient navigation system for the autonomous mobile robot demands the integration of the simultaneous localization and mapping system (SLAM). In general, the SLAM framework employs the camera, IMU, wheel encoder and can not lack the combination of the Light Detection and Ranging (LiDAR) sensors for superior accuracy for the navigation system. Nevertheless, the price of mechanical LiDAR is exceptionally high compared with other sensors, which is the primary reason to introduce a new generation of laser called Solid-State LiDAR (SSL). In this paper, we introduce a back-ground of SSL and several types of commercial SSL and also their characteristic. For developing SLAM framework, we discuss several successful SLAM architectures, which can be capable of integrating into a navigation system for the mobile robot. Last, we propose a low-cost SLAM framework using the visual-inertial-SSL, that can not only reduce the price of a mobile industrial robot but also provide excellent performance.